Fabrication of High‐Voltage Flip Chip Deep Ultraviolet Light‐Emitting Diodes Using an Inclined Sidewalls Structure. Issue 16 (4th June 2019) - Zhong, Zhibai; Zheng, Xuanli; Li, Jinchai; Zheng, Jinjian; Zang, Yashu; Lin, Wei; Kang, Junyong
Abstract : Two types of high‐voltage flip chip deep ultraviolet light emitting diodes (HV‐FC DUV‐LEDs) are constructed with 2 × 2 and 3 × 3 cells, respectively, in which each single cell is fabricated with inclined sidewalls covered by SiO2 /Al. The simulation results suggest that the structure with inclined sidewalls is much favorable to extract the transverse magnetic‐polarized lights. As a result, the light power as high as 145.7 mW is achieved in HV‐FC DUV‐LED constructed with 3 × 3 cells at 1000 mA. Abstract : High‐voltage flip chip deep ultraviolet light emitting diodes (HV‐FC DUV‐LEDs) are fabricated with inclined sidewalls covered by SiO2 /Al. High output power of 145.7 mW is realized by using such HV‐FC DUV‐LED constructed with 3 × 3 cells at 1000 mA.